Model Kepemimpinan Kepala Sekolah Dalam Menciptakan Mutu Pembelajaran Pai Di Smk Muhammadiyah 9 Medan - Naswa Kurniawan; Hadi Saputra Panggabean; Ismaraidha Ismaraidha (Journal Of Dehasen Educational Review, 2026)
This descriptive qualitative research aims to describe the principal's leadership model in creating quality Islamic Religious Education (PAI) learning at SMK Muhammadiyah 9 Medan. Through observation, interviews, and documentation methods with the principal, Ismuba teachers, and students. This study explores the leadership model as well as its supporting and inhibiting factors. This research analysis was conducted through data reduction, presentation, and drawing conclusions. The results revealed that the principal implemented a flexible, assertive, participatory leadership model, and was based on Islamic principles to ensure the quality of learning. The success of this program was supported by the dedication of the leadership, teacher competence, school policies oriented towards religious activities, and adequate facilities. However, there were significant challenges such as low learning motivation among some students, lack of support from students' families and social environments, and differences in human resource readiness in adopting learning innovations.